THE DOMINO EFFECT OF TIN CORRUPTION: ANALYSIS OF ECONOMIC GROWTH, WORKFORCE QUALITY, AND COMMUNITY WELFARE AT THE PROVINCE BANGKA BELITUNG - Fathurahman, Ezaky; Herlianto, Danil; Caressa, Dinda; Rafita, Rafita; Putri, Aning Kesuma (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
The purpose of this study is to see how corruption in the tin mining sector has an impact on economic growth, labor quality, and community welfare in the Bangka Belitung Islands Province. This study shows that using secondary data for the 2015–2023 period and the multiple linear regression method, corruption has a negative impact on the regional economy by reducing revenue used for infrastructure development and public services. The situation in the region is getting worse due to the high dependence on the mining industry which is not environmentally friendly. Agricultural and fishery yields declined due to water pollution, soil degradation, and loss of productive land. This reduces the competitiveness of other economic sectors. This causes economic growth to stagnate and society increasingly depends on fluctuations in commodity prices around the world. In addition, corruption prevents the improvement of the quality of the local workforce due to a lack of investment in skills education and training. Only a highly skilled workforce can compete in the mining sector, as non-transparent recruitment practices and nepotism exacerbate social inequality. Limited access to secondary and tertiary education reduces people's opportunities to contribute to more productive economic sectors. From a welfare perspective, corruption leads to inequality in the distribution of profits from the mining sector, which benefits a handful of economic elites, while the majority of people remain poor and face difficulties in obtaining basic services such as health and education. In addition to damaging ecosystems, uncontrolled mining exploitation reduces natural resources necessary for daily life. To improve community welfare and ensure sustainable economic growth in Bangka Belitung, this study recommends increased transparency in natural resource management, and mining governance reform